Uniting Drug and Delivery: Metal Oxide Hybrid Nanotherapeutics for Skin Wound Care - Martin T. Matter; Sebastian Probst; Severin Läuchli; Inge K. Herrmann (MDPI AG, 2020)
Wound care and soft tissue repair have been a major human concern for millennia. Despite considerable advancements in standards of living and medical abilities, difficult-to-heal wounds remain a major burden for patients, clinicians and the healthcare system alike. Due to an aging population, the rise in chronic diseases such as vascular disease and diabetes, and the increased incidence of antibiotic resistance, the problem is set to worsen. The global wound care market is constantly evolving and expanding, and has yielded a plethora of potential solutions to treat poorly healing wounds. In ancient times, before such a market existed, metals and their ions were frequently used in wound care. In combination with plant extracts, they were used to accelerate the healing of burns, cuts and combat wounds. With the rise of organic chemistry and small molecule drugs and ointments, researchers lost their interest in inorganic materials. Only recently, the advent of nano-engineering has given us a toolbox to develop inorganic materials on a length-scale that is relevant to wound healing processes. The robustness of synthesis, as well as the stability and versatility of inorganic nanotherapeutics gives them potential advantages over small molecule drugs. Both bottom-up and top-down approaches have yielded functional inorganic nanomaterials, some of which unite the wound healing properties of two or more materials. Furthermore, these nanomaterials do not only serve as the active agent, but also as the delivery vehicle, and sometimes as a scaffold. This review article provides an overview of inorganic hybrid nanotherapeutics with promising properties for the wound care field. These therapeutics include combinations of different metals, metal oxides and metal ions. Their production, mechanism of action and applicability will be discussed in comparison to conventional wound healing products.